2014
DOI: 10.1088/0953-8984/26/42/423203
|View full text |Cite
|
Sign up to set email alerts
|

The role of phonons for exciton and biexciton generation in an optically driven quantum dot

Abstract: Abstract. For many applications of semiconductor quantum dots in quantum technology a well controlled state preparation of the quantum dot states is mandatory. Since quantum dots are embedded in the semiconductor matrix, the interaction with phonons plays often a major role in the preparation process. In this review, we discuss the influence of phonons on three basically different optical excitation schemes which can be used for the preparation of exciton, biexciton, and superposition states: a resonant excita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
88
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 223 publications
(488 reference statements)
0
88
0
Order By: Relevance
“…At the highest pulse areas, however, the theory predicts essentially perfect RAP independent of the sign of the chirp. The interpretation is that the splittings between the branches at the avoided crossings are energetically so large that they lie well above the energy range of the phonons which are efficiently coupled to the exciton system [34]. In other words, the wavelength of the phonons required for scattering between the dressed states becomes much smaller than the size of the QD at high pulse area.…”
Section: -2mentioning
confidence: 99%
See 1 more Smart Citation
“…At the highest pulse areas, however, the theory predicts essentially perfect RAP independent of the sign of the chirp. The interpretation is that the splittings between the branches at the avoided crossings are energetically so large that they lie well above the energy range of the phonons which are efficiently coupled to the exciton system [34]. In other words, the wavelength of the phonons required for scattering between the dressed states becomes much smaller than the size of the QD at high pulse area.…”
Section: -2mentioning
confidence: 99%
“…We use standard GaAs parameters and take the excitation parameters from the experiment leaving the QD size as the only fitting parameter. This model has been successfully used to describe the phonon influence on Rabi rotations [34] and on the population inversion via RAP [12,27]. For the occupations of the exciton and biexciton states as well as for the coherences between all involved states a set of equations of motion is derived within a well-established fourth-order correlation expansion method [35].…”
mentioning
confidence: 99%
“…The excitonic QD states are promising candidates to be used as qubits for quantum computing [2][3][4][5][6][7] , while the radiative decay from the biexciton cascade offers the possibility of an on-demand creation of indistinguishable entangled photon pairs [8][9][10] . It has been shown that both exciton and biexciton states of a QD can be prepared by using ultra-fast laser pulses under a variety of excitation conditions 11,12 . The most commonly known schemes for this purpose are resonant excitation leading to Rabi rotations [13][14][15][16] , different protocols using chirped laser pulses exploiting the adiabatic rapid passage effect [17][18][19][20][21][22][23][24][25] , and phonon-assisted off-resonant driving [26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Quantum control of the exciton, an electron-hole pair, proceeds on picosecond timescales well before spontaneous emission takes place (timescale ∼1 ns). Phonons lead to a deterioration of the exciton preparation fidelity for schemes using resonant excitation [1,[6][7][8][9][10]. In fact, the interaction with the phonons is sufficiently strong that an exciton state can be prepared by relying on it (phonon-mediated relaxation following excitation with a detuned pulse) [11][12][13][14][15].…”
mentioning
confidence: 99%